2010
DOI: 10.1208/s12249-010-9536-3
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intra-Manufacturer Variability in Pharmaceutical Grades and Lots of Xanthan Gum

Abstract: Abstract. A pharmaceutical formulation typically contains one or more excipients in addition to the active pharmaceutical ingredient(s). Though excipients have been considered inert components of a formulation, variability in their properties has been shown to affect the performance of drug dosage forms and delivery systems. This study investigates the inter-and intra-manufacturer variability among different NF grades and lots of xanthan gum made by two manufacturers. As many formulators rely on compendial sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Results for nitrogen, ash and total glucose contents of XG samples (Table ) were similar to those previously reported (Garcia‐Ochoa et al ., ,b; Thacker et al ., ). These components are present as contaminants in XG.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Results for nitrogen, ash and total glucose contents of XG samples (Table ) were similar to those previously reported (Garcia‐Ochoa et al ., ,b; Thacker et al ., ). These components are present as contaminants in XG.…”
Section: Resultsmentioning
confidence: 97%
“…NH 4 is a better N‐source for biomass accumulation, while NO 3 is best for XG yield (Rosalam & England, ). Differences in the refining methods (of crude XG) used by manufacturers result in variation in the amount of these contaminants in XG (Thacker et al ., ; El Enshasy et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This minimum of regulatory specifications may suffice for these industries, but pharmaceutical companies have to deal more strictly with excipient variability and be assured that the properties rendering excipients functional are "present" in every batch within appropriate limits. A first issue that arises from current monograph specifications is that they cannot adequately set the appropriate limits in functional specifications ("one-point" limits [25] or a wide range of acceptance values). Without prior mechanistic knowledge of the actual excipient role, variability could be detrimental, even if excipient property values meet monograph specifications [25].…”
Section: Natural Sourcingmentioning
confidence: 99%
“…The study reported the subsequent impact of these differences on process ability and/or functionality . Thacker et al investigated the intermanufacturer and intramanufacturer variability among the different grades and lots of xanthan gum produced by two manufacturers. A significant intermanufacturer and intramanufacturer variability among the grades and lots of xanthan gum was reported in this study.…”
Section: Source‐to‐source Variationmentioning
confidence: 99%